Identifikasi Lahan Investasi Potensial Kawasan Free Trade Zone (FTZ) Bintan - Harianto, Sri; Pramana, A. Yunastiawan Eka; Yusliana, Yusliana (Institut Teknologi Nasional Yogyakarta, 2023)
Free Trade Zone (FTZ) is an area that is separate from the customs area so that it is free from the imposition of import duties, VAT, PPnBM and excise. One of the FTZ areas in Indonesia is the Bintan FTZ. Being on the side of the busiest international trade route in the world makes Bintan a gateway for the inflow of investment, goods and services to and from abroad. The availability of human resources and land as well as the commitment of the Regional Government really supports the growth of investment. So an instrument is needed for potential investors regarding the availability, distribution and condition of potential land for investment. With a descriptive-qualitative approach and using spatial analysis techniques and the accuracy of the satellite image data obtained, an academic and comprehensive instrument can be produced. Satellite image data is subjected to orthorectification and georeferencing correction to test its validity and then digitized, attribution, and attached to spatial planning regulations as well as analysis of land condition criteria that support investment to produce potential land for investment. The results of the analysis show that 1,679.53 Ha (4.23%) and 15,423.92 Ha (38.80%) of the total Bintan FTZ area falls into the very high and high potential land categories. These lands are dominated by bushes, moors and open land, have good road accessibility and high accessibility to transportation nodes for access to goods, services and labor.